A survey of zoonotic pathogens carried by Norway rats in Baltimore, Maryland, USA - Easterbrook, J. D. (2007)
Fil: Easterbrook, J. D. The Johns Hopkins Bloomberg School of Public Health. The W. Harry Feinstone Department of Microbiology and Immunology; Estados Unidos.